DEVELOPMENT OF TECHNOLOGY OF THE HIGH-QUALITY CAST IRONS PRODUCTION BY MEANS OF GRAPHITIZING MODIFICATION BY THE HIGH-POLYMERIC AMALGAMATION WASTES - A. I. Garost (Литьë и металлургия)
The variant of graphitizing modification of gray cast irons by means of application of non-classic methods of processing, when unusable for regeneration high-polymeric compounds are uses as additives. There is noted the improvement of the cast iron structure: form of graphite impurities is varying from PGd 180 up to PGD 45, the character of graphite impurities from PGr up to PGr 3, perlitization of metallic base is observed.